Post Operative Voiding Efficacy after Anterior Colporrhaphy - Behnoosh Miladpoor; Roya Kokabi; Zhila Fereidouni; Mohammad Hassan Meshkibaf (Acta Medica Iranica, 2010)
The aim of this study was to determine the most effective and suitable time to remove the urinary catheter (Foley) after anterior and posterior colporrhaphy surgery. Patients who experience anterior Colporrhaphy operation for genuine stress incontinency or pelvic organ prolapsed will have post operative voiding dysfunction. These patients need postoperative drainage. One of the methods preferred for this purpose is to apply Foley Catheter, but there is no particular regimen available for the exact time of catheter removal in these patients. We have tried to find out the best time to remove Foley catheter after which the repeated Foley catheter is not required or minimized. One hundred and eighty nine patients who have been undergone Colporrhaphy have been selected randomly and divided into three groups' as 1, 2 and 4 days of catheter removal. The number of patients in each group was 62, 63 and 64 respectively. In all three groups, before removing urinary catheter, it was clamped every 4 hrs, for 3 times. After removing of Foley, the patients were guided for urination; the voiding and residual volume was measured. In the patients with an increase of residual volume, the repeated Foley requirement was increased. However, 5.6 % of the patients with residual volume of ≤ 33 percent and 23.9% of the patients with residual volume between 33 to 68 percent, and finally 64.8% of the patients with residual volume of ≥ 68% had repeated Foley insertion. When considering the number of days, 85, 65 and 35.7 percent of the patients needed repeated Foley after 1, 2, and 4 days of catheter removal respectively. Interestingly, in the third group ( 4 days of the catheter removal ) with residual volume of ≤ 33% the repeated Foley requirement was nil, with no increase risk of urinary infection. We suggest that the best time to remove the urinary Foley catheter after anterior and posterior Colporrhaphy is the day four.